Adaptación del paciente hipertenso en el proceso de su enfermedad. abril–agosto 2018 - Pérez Ortega, Julia Sofía (2018)
The present research has as objective, to describe the relevant studies of different authors, in relation to the process of adaptation of the hypertensive patient to his disease. It is currently hypertension, a public health problem and a third cause of morbidity worldwide. The studies focus on the way in which the patient manages to adapt to their illness, the nursing staff will identify the specific factors that will help or not improve their habits and lifestyle. For the realization of the present work, 30 scientific articles were taken into account with articles published in journals, books published nationally and internationally references to the subject. After the bibliographic review, and in general terms, we can affirm that; the majority of authors start by establishing the values to be considered as arterial hypertension, with the parameter of 140/90mmHg and in what refers to the etiology eleven authors agree that the consumption of tobacco, alcohol, sedentary lifestyle, predisposition genetic factors are predisposing factors for hypertension, also three authors agreed that the body mass index (BMI) should be measured, a factor that determines that, if the patient is overweight, it can be diagnosed as hypertensive, five authors used Calista Roy’s adaptation scale for their research, since it measures the cognitive, behavioral or behavioral and emotional aspects, because it is considered that if a patient has altered any parameter of this scale, it could be concluded a medical level, that the patient has not managed to adapt to his pathology.